Disentangling the Gender Gap in Longevity - Timo Trimborn; Johannes Schünemann; Holger Strulik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In developed countries, women are expected to live about 4-5 years longer than men. In this paper we develop a novel approach in order to gauge to what extent gender health differences in longevity can be attributed to gender-specific preferences and health behavior. For that purpose we set up a physiologically founded model of health deficit accumulation and calibrate it using recent insights from gerontology. From fitting life cycle health expenditure and life expectancy we obtain estimates of the gender-specific preference parameters. We then perform the counterfactual experiment of endowing women with the preferences of men. In our benchmark scenario this reduces the gender gap in life expectancy from 4.6 to 2.1 years, suggesting that 54 percent of women's superior longevity can be attributed to preferences and health behavior. When we add gender-specific preferences for unhealthy consumption, the model can motivate up to 91 percent of the gender gap. Our theory explains also why the gender gap narrows with rising income.
Keywords: D91; J17; J26; 330